Estudio de factibilidad para la creación de una empresa dedicada al servicio de gestión de cobros para la ciudad de Loja - Quezada Sarango, Mayra del Rocío (2016)
The "Feasibility study for the creation of a company dedicated to service of collection to the city of Loja", it was what made based on the different local companies, using various methods and techniques that supported essential for gathering the information necessary to perform all required studies and the study of markets, technical study, administrative study - legal and financial study, thus fulfilling the objective raised. The first objective is accomplished by performing the market study which found that the city currently a demand for 2821 companies with nonperforming loans and are likely to acquire the services of the company's collections and an offer of 919 companies that have possessed billing department or have agreements with lawyers, resulting in a market availability of 1901, then the service is set to be provided, the price square and advertising to develop. The second objective technical study indicates the location of the company in Bolivar Street between Miguel Riofrío and Vicente Rocafuerte made through the weighting method set points, the installed capacity is determined based on the number of employees responsible for collecting, number of portfolios and capacity utilization to 80% share for year 1, in project engineering all materials needed to perform the operations within the company is denoted set. The third goal is shaped by the corporate philosophy, the structural and functional organization, the manual functions and everything concerning 5 the administrative level that is required for development of activities, the legal basis is governed under the name of limited company and complies with all the provisions of the Superintendence of Companies. In the fourth objective financial study all items required by the company are detailed obtaining an initial investment of $ 22.814,19; obtained are positive indicators, the net present value is $ 73.259,91; the internal rate of return is 116,21% is the same that is higher than the discount rate of 15,67%, the benefit cost ratio shows that for every dollar invested in the company a profit of $ 0,27 is obtained, the capital recovery period is 8 months; sensitivity analysis in relation to increased costs of 13,28% and a decrease of 9,355% revenue is 0.99%, with less than 1, denoting that the project is very profitable. Finally it is concluded that the project is feasible as it will help businesses of the city of Loja to the recovery of distressed debt due and providing a quality service that allows them to recover the working capital that was believed lost.